PEMBERDAYAAN MASYARAKAT PEDULI STROKE DENGAN PEMBENTUKAN RINTISAN PUSAT HOME CARE STROKE DAN PELATIHAN HOME CARE STROKE DI KOTA TRENGGALEK - Awan, Awan Hariyanto; Christiani, Mimik; Niningasih, Rahayu (STIKES dan AKZI Karya Husada Kediri, 2024)
Stroke is a disease with a sudden onset and causes death and disability both in urban and rural areas. The consequences of a stroke in the community include paralysis of the upper and lower limbs, vision problems, difficulty speaking and difficulty swallowing, while the psychological impact that can occur is frustration and irritability which requires treatment after a stroke. Stroke home care services providing nursing care to stroke patients after post-hospital treatment with home care are very much needed by the family. This community service method includes holding Focus Group Discussions with stakeholders and training for stroke home care cadre participants. The offline home care stroke training method, bedside teaching, was very effective in increasing the knowledge and skills of caring for stroke patients among the 12 cadre participants. After the training, 91.6% of the cadre participants' knowledge of skills increased well. From the results of the Focus Group Discussion, the formation of stroke home care is very much needed in the community. form health facilities with permits in accordance with applicable regulations. Empowering the Stroke Care Community in Efforts to Establish Stroke Home Care which is carried out through training is very effective in increasing knowledge and understanding skills in stroke home care care and its establishment and operation requires in the form of health facilities with permits in accordance with applicable regulations.